Primary radiation damages in Li2TiO3 and Li4SiO4: a comparison study using molecular dynamics simulation. Issue 3 (3rd April 2022) - Sahoo, Deepak Ranjan; Chaudhuri, Paritosh; Swaminathan, Narasimhan
Abstract : Molecular dynamics simulations are conducted on β -Li 2 TiO 3 and Li 4 SiO 4 to compare several of their radiation damage-related properties at 0 K. Overall, Li 2 TiO 3 was found to be more tolerant to irradiation damage than Li 4 SiO 4, which is in qualitative agreement with recent experiments. For instance, Li 2 TiO 3 was found to amorphize at 0.55 dpa, while Li 4 SiO 4 amorphized at 0.25 dpa itself. Including the polarization of the O atom while modeling cascades in Li 2 TiO 3 was found to predict a more realistic cascade behavior and defect production. The threshold displacement energies and diffusion coefficients of atoms were calculated for both the materials. Li diffusion was found to be highest when compared to other atoms. For Li 4 SiO 4, the existing interatomic potential predicted an Li diffusion coefficient which is nearly two orders of magnitude higher than what is seen for Li 2 TiO 3 . Moreover, this potential predicted Li diffusion at temperatures as low as 583K, making it impossible to compare finite temperature primary damage with Li 2 TiO 3 .